Machine Replacement and the Business Cycle: Lumps and Bumps - Cooper, Russell; Haltiwanger, John; Power, Laura (American Economic Review, 1999)
This paper explores investment fluctuations due to discrete changes in a plant's capital stock. The resulting aggregate investment dynamics are surprisingly rich, reflecting the interaction between a replacement cycle, the cross-sectional distribution of the age of the capital stock, and an aggregate shock. Using plant-level data, lumpy investment is procyclical and more likely for older capital. Further, the predicted path of aggregate investment that neglects vintage effects tracks actual aggregate investment reasonably well. However, ignoring fluctuations in the cross-sectional distribution of investment vintages can yield predictable nontrivial errors in forecasting changes in aggregate investment. (JEL E22, E32)